THE INFLUENCE OF LATTICE STRAIN TO THE CRITICAL CURRENT DENSITY OF YBCO - Engkir Sukirman; Didin S. Winatapura; Wisnu Ari Adi; Yustinus Purwatamanggalapratala (Jurnal Sains Materi Indonesia, 2007)
THE INFLUENCE OF LATTICE STRAIN TO THE CRITICAL CURRENT DENSITY OF YBCO. The influence of lattice strain to the critical current density of YBCO have been investigated. In this investigation it were prepared the YBCO superconductor samples which made by using a modified melt-textured growth (MMTG) method. The aim of doing this research is to investigate the relation between the critical current density and the lattice strain in YBCO superconductor. The structural and microstructural properties of the samples were characterized by the x-ray diffraction technique. The diffraction data were analyzed by means of a RIETAN software. While, the electrical properties of each samples were characterized by four point probe method. The lattice strains were then determined using the formula : <e2 hkl> = (U - Uo)/32 ln 2, where U is the refined FWHM parameters of the broadened peak due to the presence of an inhomogeneous strain field and U0 is the one due to the instrumental resolution only. The result of analysis indicate that the critical current densities and the lattice strains in YBCO samples have inversed correlation, i.e.when the lattice strain decreases, critical current increases, and conversely. The melt-process through 12 minutes may have possibly eliminated the weak links. Therefore, the critical current density increases, and the lattice strain decreases.